2010
DOI: 10.1038/oby.2009.316
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Prevents Regain of Visceral Fat for 1 Year Following Weight Loss

Abstract: The purpose of this study was to determine what effect aerobic and resistance exercise training has on gain of visceral fat during the year following weight loss. After being randomly assigned to aerobic training, resistance training, or no exercise training, 45 European‐American (EA) and 52 African‐American (AA) women lost 12.3 ± 2.5 kg on a 800 kcal/day diet. Computed tomography was used to measure abdominal subcutaneous and visceral adipose tissue, whereas total fat and regional fat (leg, arm, and trunk) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 39 publications
3
127
0
9
Order By: Relevance
“…The majority of the studies focused on obese subjects, with the exception of Hunter et al (49) and Nakade et al (57) who included both obese and overweight subjects. The studies were different in PA by demographic characteristics.…”
Section: Physical Activity and Weight Regainmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies focused on obese subjects, with the exception of Hunter et al (49) and Nakade et al (57) who included both obese and overweight subjects. The studies were different in PA by demographic characteristics.…”
Section: Physical Activity and Weight Regainmentioning
confidence: 99%
“…It should be underlined that sex differences between energy expenditure related to PA, appetite ratings and energy intake may lead to different patterns of energy intake and subsequent weight maintenance (61) . Very few reviewed intervention studies have explored whether the programmes based on diet and exercise gave better results regarding anthropometry than the use of one method alone (49,(57)(58)(59) . Often the PA is much more difficult to perform by obese subjects, because performance is related to public places.…”
Section: Physical Activity and Weight Regainmentioning
confidence: 99%
“…Furthermore, a meta-analysis pooling data from progressive resistance exercise training studies in normotensive or hypertensive adults showed small but significant reductions in percent body fat without changes in body weight [11]. Interestingly, Hunter et al [12] showed that 80 min/wk of aerobic or resistance exercise prevented weight regain at 1-year follow-up, especially visceral fat, following a diet-induced weight loss program in overweight premenopausal women aged 21 to 46 years. Some resistance training studies in individuals with type 2 diabetes found reductions in waist circumference [13] and trunk adiposity [14] whereas others did not [15].…”
Section: Effects On Total Body Fat and Abdominal Adipositymentioning
confidence: 97%
“…O treinamento físico aeróbico tem sido constantemente recomendado para controle de peso corporal, prevenção e tratamento não farmacológico da obesidade, especialmente por promover aumento do gasto energético e, consequentemente, interferir diretamente no balanço energético (IRVING et al,2008;HUNTER et al,2009). Estudos publicados na literatura demonstraram que o treinamento físico favorece o uso de lipídios como fonte de energia, reduzindo, assim, a adiposidade e garantindo menor peso corporal (LIMA-SILVA et al, 2006;KEITH et al, 2006;GOLLISCH et al, 2009 Células adiposas expressam ambos receptores β e α-adrenérgicos.…”
Section: Discussionunclassified